Provision of quality education in the context of Syrian refugee children in the UK: opportunities and challenges - Madziva, Roda; Thondhlana, Juliet (Taylor & Francis, 2017)
While existing research has shown the importance of the three interrelated domains of the wider policy, the school and home/community environments in the development of quality education for learners, this literature does not fully capture the experiences of the refugee population. In this article we focus on a group of Syrian refugees that came as part of the first large cohort that was welcomed in the UK in December 2015. We adapt Tikly’s quality education frameworks and develop a model that highlights not only the importance of the three intersecting environments, but also the specific inputs/processes that are critical to achieving quality education for refugees. In so doing, we stress the critical role of English as a tool for refugee children’s inclusion and integration in schools. Consequently, the contribution of the paper is an understanding of the inputs/processes that are key to the development of quality education for migrant/refugee children.